2022
DOI: 10.1039/d1sm01550h
|View full text |Cite
|
Sign up to set email alerts
|

DC electric field-driven heartbeat phenomenon of gallium-based liquid metal on a floating electrode

Abstract: The heart beating phenomenon of room temperature liquid metal (LM) mercury has attracted much attention in the past years, but its research and application are limited because of the low...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…3(e)). A redox reaction 34,43,44 occurs on the surface of the LMDs, in which the near negative side of the droplet undergoes an oxidation reaction to produce Ga 2 O 3 .2Ga + 6OH − = Ga 2 O 3 + 3H 2 O + 6e − …”
Section: Resultsmentioning
confidence: 99%
“…3(e)). A redox reaction 34,43,44 occurs on the surface of the LMDs, in which the near negative side of the droplet undergoes an oxidation reaction to produce Ga 2 O 3 .2Ga + 6OH − = Ga 2 O 3 + 3H 2 O + 6e − …”
Section: Resultsmentioning
confidence: 99%
“…Under the stimulation of an external field, Wang et al constructed a circular graphite electrode tilted at an angle in a NaOH solution, to realize a voltage-stimulated oscillation with liquid gallium . Ge et al reported a gallium indium alloy heartbeat on a floating electrode with the stimulation of a direct current field . Li et al designed an artificial heart based on eutectic GaInSn metal alloy with an electric field excitation device …”
Section: Introductionmentioning
confidence: 99%
“…19 Ge et al reported a gallium indium alloy heartbeat on a floating electrode with the stimulation of a direct current field. 20 Li et al designed an artificial heart based on eutectic GaInSn metal alloy with an electric field excitation device. 21 In our recent study, we introduced another safer substitute for the MBH demonstration: the Galinstan beating heart demonstration (GBH).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Gallium-based LMs, such as eutectic gallium indium alloy (EGaIn, 75.5 wt% gallium and 24.5 wt% indium) and Galinstan (68.5 wt% gallium, 21.5 wt% indium, and 10 wt% tin), are a new kind of intelligent material that combines the characteristics of metals and fluids, such as excellent thermal conductivity, 9 electrical conductivity, 10–12 fluidity, 13 biocompatibility, 14 and low toxicity. 15 The LM applications in flexible robots, 16,17 flexible electronics, 18,19 micromotors, 20,21 neural probes, 22 drug delivery, 23–25 chip cooling, 26 3D printing, 27–29 liquid metal pumps 30 and other fields 31–34 have attracted much attention. In addition, LM droplets can move under the action of ultrasound, 35 optical, 36,37 electrical, 38,39 magnetic, 40–42 and chemical mechanisms, 20 which makes LMs have great applications in microfluidics and robotics.…”
Section: Introductionmentioning
confidence: 99%